Evidence for Short Temporal Atmospheric Variations Observed by Infrasonic Signals: 1. The Troposphere. Issue 3 (1st March 2022) - Averbuch, G.; Ronac‐Giannone, M.; Arrowsmith, S.; Anderson, J. F.
Abstract: Infrasound monitoring is used in the forensic analysis of events, studying the physical processes of sources of interest, and probing the atmosphere. The dynamical nature of the atmosphere and the use of infrasound as a forensic tool lead to the following questions; (1) what is the timescale of atmospheric variability that affects infrasonic signals? (2) how do infrasound signals vary as a function of time? This study addresses these questions by monitoring a repetitive infrasound source and its corresponding tropospheric returns 54 km away. Source‐receiver empirical Green's functions are obtained every 20 s and used to demonstrate the effect of atmospheric temporal variability on infrasound propagation. In addition, observations are compared to predicted simulated signals based on realistic atmospheric conditions. Based on 127 events over 3 days, it is shown that infrasound properties change within tens of seconds. Particularly, phases can appear and disappear, the propagation time varies, and the signals' energy fluctuates. Such variations are attributed to changes in temperatures and winds. Furthermore, atmospheric models can partly explain the observed changes. Therefore, this study highlights the potential of high temporal infrasound‐based atmospheric sounding. Key Points: Evidence for temporal (minute‐scale) variability of the lower troposphere is observed by infrasound Short temporal dynamics affects infrasonic phases, waveforms, propagation time, and energy